2020
DOI: 10.1007/s00248-020-01507-8
|View full text |Cite
|
Sign up to set email alerts
|

DMSP-Producing Bacteria Are More Abundant in the Surface Microlayer than Subsurface Seawater of the East China Sea

Abstract: Microbial production and catabolism of dimethylsulfoniopropionate (DMSP), generating the climatically-active gases dimethyl sulfide (DMS) and methanethiol (MeSH), have key roles in global carbon and sulfur cycling, chemotaxis and atmospheric chemistry. Microorganisms in the sea surface microlayer (SML), the interface between seawater and atmosphere, likely play an important role in the generation of DMS and MeSH and their exchange to the atmosphere, but little is known about these SML microorganisms. Here, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
50
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(59 citation statements)
references
References 90 publications
8
50
1
Order By: Relevance
“…Indeed, similar metagenomics studies with greater sequencing depth (eight-fold) on surface seawater did detect DSYB and TpMMT [53]. It is also noteworthy that qPCR data on other ECS samples [57] demonstrated that DMSP-producing bacteria with dsyB were also present in the >3 µm seawater samples, indicating that larger bacteria or bacteria tightly associated to phytoplankton may also be contributing to the DMSP levels detected in this fraction.…”
Section: Discussionmentioning
confidence: 53%
“…Indeed, similar metagenomics studies with greater sequencing depth (eight-fold) on surface seawater did detect DSYB and TpMMT [53]. It is also noteworthy that qPCR data on other ECS samples [57] demonstrated that DMSP-producing bacteria with dsyB were also present in the >3 µm seawater samples, indicating that larger bacteria or bacteria tightly associated to phytoplankton may also be contributing to the DMSP levels detected in this fraction.…”
Section: Discussionmentioning
confidence: 53%
“…2013; Teeling, et al . 2012), which are known to be dominant in the SML (Sun, et al . 2020) and on transparent exopolymer particles (Zäncker, et al .…”
Section: Discussionmentioning
confidence: 99%
“…Labile organic matter particularly selects for fast-growing, opportunistic, and active bacteria in foams such as Gammaproteobacteria (Landa, et al 2013;Teeling, et al 2012), which are known to be dominant in the SML (Sun, et al 2020) and on transparent exopolymer particles (Zäncker, et al 2019). For instance, Alteromonas sp., of which we found an OTU among the free-living bacteria present in Trichodesmium foam ( Supplementary Table 4), were previously shown to be highly abundant and active degraders of alginate, a cell wall component from marine macroalgae (Mitulla, et al 2016), and of labile dissolved organic carbon (Pedler, et al 2014).…”
Section: Gammaproteobacteriamentioning
confidence: 99%
“…Thalassospira and Novosphingobium are typical DMSP-producing genera with mmtN ( Williams et al, 2019 ). With the exception of TpMMT, which has only been studied in T. pseudonana , the other S -methyltransferase genes in algae and bacteria serve as reliable reporters for DMSP synthesis in diverse marine environments ( Curson et al, 2017 ; Kageyama et al, 2018 ; Williams et al, 2019 ; Sun et al, 2020 ; Zheng et al, 2020 ). Approximately 0.35% of marine bacteria contain dsyB and are predicted to make DMSP, whereas mmtN is far less abundant ( Williams et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Phytoplankton, such as dinoflagellates, haptophytes, and green algae that contain the highest intracellular DMSP levels ( Keller et al, 1989 ; Curson et al, 2018 ), are believed to be the main oceanic DMSP producers ( Zhang et al, 2019 ). However, recent studies analyzing the prevalence key algal and bacterial DMSP synthesis genes in environmental samples suggest that bacteria also significantly contribute to marine DMSP production ( Williams et al, 2019 ; Song et al, 2020 ; Sun et al, 2020 ; Zheng et al, 2020 ; Liu et al, 2021 ), especially in aphotic and deep seawater and surface marine sediments where phytoplankton are scarce.…”
Section: Introductionmentioning
confidence: 99%